A review of important medical and surgical considerations for obese patients undergoing arthroscopic surgery. Issue 3 (2nd July 2016) - Prodromo, John; Rackley, Justin; Mulcahey, Mary K.
ABSTRACT: Obesity represents a unique challenge in orthopaedic surgery, the impact of which is seen through all phases of injury: in the development of disease, during the operative procedure, and throughout the rehabilitation period. Given the high prevalence of obesity in the United States and around the world, this patient population represents a substantial proportion of patients in need of orthopedic care. The effects of this disease constrain both medical and financial resources. For obese patients undergoing orthopedic procedures, adequate steps must be taken to minimize the risks that occur before, during, and after surgical intervention. This literature review discusses the impact of obesity on arthroscopic procedures, with a focus on procedures involving the shoulder, hip, and knee. The management of obese patients during the perioperative period should address the specific concerns relating to these patients. Obesity is a risk factor for numerous comorbidities, is associated with surgical complications, and is a predictor of poor functional outcomes following arthroscopy. Efforts to minimize the negative impact of obesity on arthroscopic procedures are crucial.